KEPENTINGAN EKONOMI POLITIK TIONGKOK DALAM PEMBENTUKAN BANK INVESTASI INFRASTRUKTUR ASIA (AIIB) DI NEGARA-NEGARA ASEAN - Achmad Giffari Gibran; Saiman Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research explain about the Interest of Chinese’s Government for founding a new multinational Bank like Asian Infrastructure Investmen Bank in Southeast Asia. The Chinese Government aims to increase their Political and economical influence in ASEAN countries..In this research the authors use the perspective of Mercantilism. International Relations is a study of the interaction between several actors participating in international politics that include countries, international organizations, non-governmental organizations in the economic field that can be defined as a sustainable formal structure whose formation is based on agreements between its members (government and non-government) from two or more sovereign states with the aim of achieving the common goals of its members., sub-national entities such as bureaucracy and the domestic government as well as individuals. Given the Mercantilism perspective that has been put forward, the level of analysis used by the author is the level of state interest or national interest analysis. In this study the authors use the concept of National Interest and the concept of Sphere of Infuience. National interest means: “The values, desires and interests which states seek to protect or achieve in relation to each other” “desires on the part of sovereign states”. While Sphere of Influence means a claim by a State to exclusively or predominant control over a foreign area or territory. It can be concluded from this research that the Chinese government obejctives from creating AIIB are for increasing their economic and politic interest in ASEAN countries, as those country have a strategic value for China in economy and China geopolitical ambition to make that region as their Sphere of Influence.Keywords : AIIB (International Tripartite Rubber Council), Economic Interest, Political Interest, Sphere of Influences, Infrastructure